Escape! : a novel [large type] - Fishbach, Stephen (Random House Large Print, 2026)
"Everybody gets the story arc they deserve. Kent Duvall, a has-been reality winner, just wants another chance at glory--to find his way out of his depressing life and back to his highlight reel. When a scandal is captured on camera at a charity event, he gets his shot, on a remote island with seven other contestants. Each has been cast as a type--Ruddy the bully, Miriam the nerd, Ashley the love interest--but every one of them is more than they seem. The contestants' goal seems simple--survive the wild, build a raft, win treasure. But Beck Bermann, a disgraced reality producer, sees them as characters in her own redemption arc. As the schemes and strategies spiral out, breakout camps sabotage each other, and rival producers struggle to control the storyline. Soon, the question becomes less about who will win than who will make it out in one piece." --